Analysis of Egg Production Forecasting by Province in Indonesia Using the ARIMA Algorithm - Khaswa Giovani Simanungkalit; Muhammad Fikri Azhari; Muhammad ihsan Raditya; Indra Lesmana Putra; Victor Asido Elyakim P (Yayasan Literasi Sains Indonesia, 2025)
The production of chicken eggs in various regions of Indonesia shows significant variations over time, making it necessary to apply an appropriate predictive approach to support national food planning and distribution strategies. This study employs the ARIMA (AutoRegressive Integrated Moving Average) method to forecast regional chicken egg production based on secondary data from 2018 to 2024. The research steps include data collection, stationarity testing, model parameter determination, as well as the modeling process and result evaluation. The predictions indicate that total national chicken egg production will experience a significant increase, from 12.5 billion eggs in 2025 to 18.57 billion eggs in 2026. Provinces on the island of Java, such as East Java, Central Java, and West Java, are expected to remain the main production centers. Meanwhile, provinces in eastern Indonesia show less stable prediction results, indicating the need for improved data quality and the application of more adaptive models. Overall, the ARIMA model is considered effective for modeling short-term trends, although it has limitations in handling data with high fluctuations.